Bacterial Isolates and its Antibiotic Susceptibility Pattern in NICU - Shrestha, S; Shrestha, NC; Dongol Singh, S; Shrestha, RPB; Kayestha, S; Shrestha, M; Thakur, NK (Kathmandu University Medical Journal, 2014)
Background Neonatal sepsis is one of the major causes of morbidity and mortality among the newborns in the developing world. Objectives To determine the common bacterial isolates causing sepsis in neonatal intensive care unit and its antibiotic susceptibility pattern. Methods A one year discriptive prospective study was conducted in neonatal intensive care unit to analyse the results of blood culture and to look into the sensitivity of the commonly used antibiotics. Results The blood culture yield by conventional method was 44.13% with nosocomial sepsis accounting for 10.79%. 84.08% were culture proven early onset sepsis and 15.95% were late onset sepsis. Klebsiella infection was the commonest organism isolated in early, late and nosocomial sepsis but statistically not significant. Gram positive organisms were 39.36% in which Staphylococcus aureus was the leading microorganism followed by coagulase negative staphylococcus areus. Gram negative organisms were 60.64% amongst them Klebsiella was the most often encountered followed by Pseudomonas. The most common organism Klebsiella was 87.5% and 78.3% resistance to ampicillin and gentamycin respectively. Among gram negative isolates 87.5% and 77.2% were resistance to ampicillin and gentamycin respectively. Among gram positive isolates 58.5% and 31.5% resistance were noted to ampicillin and gentamycin respectively. Resistance to cefotaxim to gram negative and gram positive isolates were 87.34% and 59.35% respectively. Conclusion Klebsiella is most common organism which is almost resistance to first line antibiotics. Resistance to both gram negative and gram positive isolates among firstline antibiotics and even with cefotaxim is emerging and is a major concern in neonatal intensive care unit. DOI: http://dx.doi.org/10.3126/kumj.v11i1.11030 Kathmandu University Medical Journal Vol.11(1) 2013: 66-70